2023
DOI: 10.1039/d2ce01254e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CO2 on the crystallization of poly(lactic acid) homo-crystallites via influencing the crystal structure of stereocomplex crystallites

Abstract: The crystallization of poly(lactic acid) (PLA) homo-crystallites (HC) and stereocomplex crystallites (SC) is quite complicated for the inducing and competing effects of SC on HC. Furthermore, carbon dioxide (CO2) would...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…It has been demonstrated that the foaming conditions, such as foaming temperature and time, blowing agent concentration, and saturation time, greatly affect the crystallinity, density, and dimensional stability of PLA foams [238]. Particularly, the dissolved gas used in foaming has great influence on the crystallization and melting behaviours of PLA [239,240]. Among the gases commonly used in PLA foaming, CO 2 is much more soluble in PLA compared to N 2 [39,76].…”
Section: Poly (Lactic Acid) (Pla)mentioning
confidence: 99%
“…It has been demonstrated that the foaming conditions, such as foaming temperature and time, blowing agent concentration, and saturation time, greatly affect the crystallinity, density, and dimensional stability of PLA foams [238]. Particularly, the dissolved gas used in foaming has great influence on the crystallization and melting behaviours of PLA [239,240]. Among the gases commonly used in PLA foaming, CO 2 is much more soluble in PLA compared to N 2 [39,76].…”
Section: Poly (Lactic Acid) (Pla)mentioning
confidence: 99%
“…24,25 As a non-toxic, green and environmentally friendly solvent, carbon dioxide (CO 2 ) could penetrate into the molecular chain of polymer, act as a compatible diluent, reduce the concentration of the molecular chain, weaken the interactions between molecular chains and promote the movement of the molecular chain, thus affecting the crystallization of the polymer, which could alter the crystallization kinetics, crystal form and spherulite morphology of polymer. [26][27][28][29][30][31][32][33][34][35] Li et al 36 found that PEO-b-PCL formed common spherulites under air, and generated ring band spherulites under CO 2 . As CO 2 pressure increased, the formation mechanism of ring band spherulite changed from periodic twisting of lamellae to two-step growth.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to introducing polymers as compatible diluents, organic solvents could also serve as compatible diluents to enhance the unbalanced stress of polymer, leading to form ring band spherulite 24,25 . As a non‐toxic, green and environmentally friendly solvent, carbon dioxide (CO 2 ) could penetrate into the molecular chain of polymer, act as a compatible diluent, reduce the concentration of the molecular chain, weaken the interactions between molecular chains and promote the movement of the molecular chain, thus affecting the crystallization of the polymer, which could alter the crystallization kinetics, crystal form and spherulite morphology of polymer 26–35 . Li et al 36 found that PEO‐b‐PCL formed common spherulites under air, and generated ring band spherulites under CO 2 .…”
Section: Introductionmentioning
confidence: 99%